(untitled) (Swiss Medical Weekly, 2011)
AIMS: To describe the involvement and input of physicians and nurses in cardiopulmonary resuscitation (CPR / do not attempt resuscitation (DNAR) decisions; to analyse decision patterns; and understand the practical implications. DESIGN: A Qualitative Grounded Theory study using one-time open-ended interviews with 40 volunteer physicians and 52 nurses drawn from acute care wards with mixes of heterogeneous cases in seven different hospitals in German-speaking Switzerland. RESULTS: Establishing DNAR orders in the best interests of patients was described as a challenging task requiring the leadership of senior physicians and nurses. Implicit decisions in favour of CPR predominated at the beginning of hospitalisation; depending on the context, they were relieved/superseded by explicit DNAR decisions. Explicit decisions were the result of hierarchical medical expertise, of multilateral interdisciplinary expertise, of patient autonomy and/or of negotiated patient autonomy. Each type of decision, implicit or explicit, potentially represented a team consensus. Non-consensual decisions were prone to precipitate personal or team conflicts, and, occasionally, led to non-compliance. CONCLUSION: Establishing DNAR orders is a demanding task. Reaching a consensus is of crucial importance in guaranteeing teamwork and good patient care. Communication and negotiation skills, professional and personal life experience and empathy for patients and colleagues are pivotal. Therefore, leadership by experienced senior physicians and nurses is needed and great efforts should be made with regard to multidisciplinary education.